2020
DOI: 10.1097/gox.0000000000003204
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Thickness in Crouzon–Pfeiffer Syndrome: Findings in Relation to Primary Cranial Vault Expansion

Abstract: Background: Episodes of intracranial hypertension are associated with reductions in cerebral cortical thickness (CT) in syndromic craniosynostosis. Here we focus on Crouzon–Pfeiffer syndrome patients to measure CT and evaluate associations with type of primary cranial vault expansion and synostosis pattern. Methods: Records from 34 Crouzon–Pfeiffer patients were reviewed along with MRI data on CT and intracranial volume to examine associations. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…[39][40][41][42] Furthermore, investigation of the brain structure in lambdoid suture synostosis demonstrated that patients exhibit cortical thinning of the cingulate gyrus, an area highly involved in motor function. 43,44 Although it is unclear whether the thinning is attributable to occipital pressure or a genetic defect, a similar phenomenon may Plastic and Reconstructive Surgery • September 2023 496e underlie our findings in DP. This is an area that may benefit from further investigation.…”
Section: Discussionmentioning
confidence: 65%
“…[39][40][41][42] Furthermore, investigation of the brain structure in lambdoid suture synostosis demonstrated that patients exhibit cortical thinning of the cingulate gyrus, an area highly involved in motor function. 43,44 Although it is unclear whether the thinning is attributable to occipital pressure or a genetic defect, a similar phenomenon may Plastic and Reconstructive Surgery • September 2023 496e underlie our findings in DP. This is an area that may benefit from further investigation.…”
Section: Discussionmentioning
confidence: 65%
“…Total ICV was exported from FreeSurfer as ‘eTIV’ via the ‘mri_segstats’ command. These techniques have previously been applied with success in the population with craniosynostosis 13,14 …”
Section: Methodsmentioning
confidence: 99%
“…These techniques have previously been applied with success in the population with craniosynostosis. 13,14 Scaling coefficient Objects of invariant shape but variable size demonstrate a geometric scaling relationship which can be expressed as: s=kv a (where s=surface area, v=volume, k=constant, and a=2/3 is a scaling exponent). 5 The coefficient a can be obtained by log transformation yielding: log(s)=a log(v)+log (k) Therefore, plotting log(v) and log(s) by linear regression, the slope of the line is equal to a with the intercept equal to log(k).…”
Section: Cortical Volume Csa and Icvmentioning
confidence: 99%